Cote d'Ivoire : Enhanced Heavily Indebted Poor Countries (HIPC) Initiative; Preliminary Document. (IMF Staff Country Reports; Country Report ;, 2009)
This paper discusses Cote d'Ivoire's preliminary assessment of eligibility for assistance under the Enhanced Heavily Indebted Poor Countries Initiative. The March 2007 Ouagadougou Political Accord provides a roadmap for reunification, national reconciliation, demobilization, and presidential elections. Fiscal consolidation has generated fiscal space while reducing external and domestic arrears. Significant revenue collection efforts and overall expenditure restraint have resulted in a modest primary basic surplus in 2007 and a similar outcome is foreseen for 2008.